2018
DOI: 10.1016/j.gore.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, hope and flourishing are inversely associated with burnout among members of the Society for Gynecologic Oncology

Abstract: PurposeIn this study we sought to: 1) determine rates of burnout and other associated indices of psychosocial distress such as alcohol and substance abuse, 2) establish the baseline performance of gynecologic oncologists on several positive psychology metrics, 3) determine if increased hope, resilience, and flourishing are associated with decreased burnout.MethodsA survey of members of the Society of Gynecologic Oncology (SGO) was conducted in spring of 2017. Participants were sent an electronic questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 19 publications
1
24
1
1
Order By: Relevance
“…Optimism is needed for HCWs to see the world as a positive place, accepting and handling difficulties as a challenge not a barrier and as a consequence this will improve their functioning level, patients' satisfaction, and therapeutic outcome. So working hard is associated with strong hope, resilience, and optimism (38)(39)(40). The present findings reported that working excessively is more likely to be associated with psychophysical exhaustion and this agrees with Delgado et al (35) and Andreassen et al (41).…”
Section: Relation Between Workaholism Mental Health and Quality Of supporting
confidence: 92%
“…Optimism is needed for HCWs to see the world as a positive place, accepting and handling difficulties as a challenge not a barrier and as a consequence this will improve their functioning level, patients' satisfaction, and therapeutic outcome. So working hard is associated with strong hope, resilience, and optimism (38)(39)(40). The present findings reported that working excessively is more likely to be associated with psychophysical exhaustion and this agrees with Delgado et al (35) and Andreassen et al (41).…”
Section: Relation Between Workaholism Mental Health and Quality Of supporting
confidence: 92%
“…First, studies such as Redelinghuys, Rothman, and Botha [ 42 ] have found high levels of flourishing in teachers to be related to a lower likelihood of leaving the profession, a factor that is associated with one of the burnout dimensions, a lack of professional accomplishment. Second, studies with other professions [ 43 ] have found an inverse relationship between flourishing and burnout. Third, the idea of flourishing as a negative predictor of teacher burnout links conceptually with the positive psychology approach, which emphasizes the idea that flourishing represents the mirror opposite of the symptoms of common mental disorders [ 9 ], and as such is the best guarantee of preventing or reducing these pathologies (e.g., burnout).…”
Section: Introductionmentioning
confidence: 99%
“…A reziliencia és a kiégés összefüggéseinek vizsgálata számos kutatás tárgyául szolgált [24][25][26]. Vetter és mtsai onkológusok körében folytatott friss, 2018. évi kutatásukban -jelen vizsgálatunk eredményeihez hasonlóanúgy találták, hogy a reziliencia hiánya szoros összefüggést mutat a kiégés magasabb arányával [27]. E vizsgálatok megerősítik azt a feltevést, hogy a munkakörnyezet és a személyiségtényezők kölcsönös egymásra hatásának nagy szerepe van a kiégés alakulásában.…”
Section: A Reziliencia Alakulása a Vizsgált Mintábanunclassified